Gambaran Epidemiologis Tuberkulosis Paru Periode 2020-2021 di Puskesmas Kecamatan Cempaka Putih dan Tinjauannya Menurut Pandangan Islam - Mustika Alamanda, Dinda; Maulidya Sari, Siti; Arsyad, Muhammad (Jurnal Indonesia Sosial Sains, 2023)
Pulmonary tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Based on the 2018 Riskesdas, Central Jakarta has the highest prevalence in DKI Jakarta Province. This research is a descriptive quantitative study using medical record data on the incidence of pulmonary TB at the Cempaka Putih District Health Center in the period 2020 to 2021 using a sampling technique with total sampling approach. From the results of the study, it was found that the most were in the age category of 15-35 years (55.7%) and the least were in the category <15 years (10.3%). Male sex 54 people (55.7%) and female sex 43 people (44.3). The residence of the patients was 80 people (82.5%) in the Cempaka Putih District and 17 people (17.5%) outside the Cempaka Putih District area. Most were diagnosed from January to April 2020 (23.7%), and there were 3 patients with pulmonary TB who were reactive with HIV. The incidence of pulmonary TB patients was 97 people with 44 people (45.4%) diagnosed in 2020 and 53 people (54.6%) diagnosed in 2021. The highest incidence of pulmonary TB was in the age group 15-35 years (55.7 %), male sex (55.7%), living with TB sufferers in the Cempaka Putih District area (82.5%), most were diagnosed in January to April 2020 (23.7%), and there were 3 HIV reactive pulmonary TB patients.